Online afterlives immortality, memory, and grief in digital culture - Sisto, Davide 1978- (The MIT Press, 2020)
"An extended essay exploring how modern digital culture-especially social media-has changed our understanding and experience of death, memory and grieving"--
"Original Italian edition: ©2018 Bollati Boringhiere editore, Torino"--Title page verso
Keywords: Tod; Neue Medien; Totengedächtnis; Informationsgesellschaft; Digitaler Nachlass; Trauerarbeit; Death / Social aspects; Online social networks / Social aspects; Internet / Social aspects